IMAGERY IN JULIANNE MACLEAN’S THE COLOR OF HEAVEN: types of imagery, purpose of imagery, The Color of Heaven - Lestysiana Dwi Sevtira (Fakultas Sastra Universitas Gresik, 2022)
This thesis discuses about imagery existed in Julianne MacLean’s novel “The Color of Heaven”. “The Color of Heaven” is a novel that tells about Sophie Duncan’s life and there are lots of imagery used in it. The objectives of this thesis are to find imageries in the novel, to identify and classify the types of imagery, and reveal the purposes of the imagery. The thesis writer uses Laurence Perrine’s theory through Johnson & Arp (2016) about seven types of imagery which are visual imagery, auditory imagery, olfactory imagery, tactile imagery, organic imagery, and kinesthetic imagery. The thesis writer uses qualitative research design since the analysis explores about the types and the purpose of the imagery. The study uses formalism approach because the analysis is based on the thesis writer’s opinion and perception.The data are collected straight from the book by reading it for several times and taking notes the sentence that reflects about imagery, then categorize the data into its imagery types in the form of list. The result of the analysis show that there are found six types of imagery except one that is gustatory imagery. There are 32 visual imagery, 34 auditory imagery, 12 olfactory imagery, 11 tactile imagery, 16 organic imagery, and 18 kinesthetic imagery found in the novel.